Language learning strategies in relation to advanced Chinese vocabulary and writing proficiency - Liu, Xinqin; Mai, Mohammed Y.M. (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study investigated the relationship between the language learning strategies (LLSs) employed by international undergraduate students at universities in Qinghai Province, China, and their proficiency in advanced Chinese vocabulary and writing. Data was collected from 45 advanced-level students selected through purposive sampling, using Oxford’s strategy inventory for language learning (SILL), an advanced Chinese vocabulary knowledge test, and advanced Chinese writing test scores. The descriptive analysis revealed moderate language learning strategy usage, with a preference for speaking and listening development. This result indicates a limited strategy usage. The correlation analysis showed no significant relationship between strategy usage and advanced Chinese vocabulary or writing proficiency. However, a strong relationship was observed between advanced Chinese vocabulary and writing proficiency. The absent relationship between strategy usage and proficiency levels suggests insufficient Chinese language proficiency among the students. The significant relationship highlights the crucial role of vocabulary in enhancing Chinese writing skills. The results provide practical insights for enhancing the use of strategies and vocabulary teaching to improve advanced writing and Chinese proficiency among international undergraduate students.